Role of intensive rehabilitation in spastic cerebral palsy (Bangladesh Medical Journal, 2016)
Cerebral palsy is the most common childhood disability with a prevalence of 1.5 to 3 per 1000 live births. Spasticity is one of the common features of cerebral palsy as it contributes to limitations in body structure and function, leading to deformity. The treatment of cerebral palsy is multifactorial. In this study we find out the efficacy of intensive rehabilitation in the treatment of spastic cerebral palsy. This observational study was conducted over 30 patients in Dhaka Medical College Hospital from January 2011 to December 2011.The patient satisfying the inclusion and exclusion criteria was randomly enrolled in this study. They received intensive rehabilitation 1 hour daily five times a week for 24 weeks. All patients were followed up at 4 weeks interval and were evaluated for a total of 24 weeks. Intensive rehabilitation is effective in reducing tone in spastic cerebral palsy by using Modified ashworth scale (p